1989
DOI: 10.1046/j.1537-2995.1989.29589284134.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of ultraviolet light in the preparation of platelet concentrates

Abstract: Passenger lymphocytes in platelet concentrates (PCs) may induce the formation of lymphocytotoxic antibodies (LCTAbs) and subsequent refractoriness to platelet transfusions. Ultraviolet (UV) irradiation can prevent lymphocytes' acting as stimulator or responder cells in mixed-lymphocyte reactions (MLRs) and could theoretically prevent LCTAb formation in vivo. A system has been devised for the delivery of UV irradiation to PCs; platelet storage characteristics and MLRs were evaluated in UV-irradiated PCs harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…A series of studies confirmed that UVR irradiated lymphocytes were not able to induce allogeneic cells in a mixed lymphocyte culture (MLC) as first reported by Lindahl-Kiessling [4850]. Clusters formed by specialized accessory cells such as dendritic cells (DC), after mitogenic or allogenic stimulation, were necessary for lymphocyte activation to occur.…”
Section: Mechanisms Of Action Of Ubimentioning
confidence: 53%
“…A series of studies confirmed that UVR irradiated lymphocytes were not able to induce allogeneic cells in a mixed lymphocyte culture (MLC) as first reported by Lindahl-Kiessling [4850]. Clusters formed by specialized accessory cells such as dendritic cells (DC), after mitogenic or allogenic stimulation, were necessary for lymphocyte activation to occur.…”
Section: Mechanisms Of Action Of Ubimentioning
confidence: 53%
“…[4749]. Clusters formed by specialized accessory cells after mitogenic or allogenic stimulation, with dendritic cells (DC) are necessary for lymphocyte activation to occur.…”
Section: Mechanisms Of Action Of Ubimentioning
confidence: 99%
“…Our group has shown that the UVA alone does not contribute to the changes in aggregation response observed in INTERCEPT‐treated PLTs compared to untreated PLTs . The effect of UVB on PLTs is better documented as UVB radiation alone has been used to prevent alloimmunization and refractoriness to PLT transfusions caused by contaminating WBCs in PCs . These studies have shown significant differences in PLT aggregation for a UVB dose equal or superior to 3 J/cm 2 in response to collagen, ADP, and arachidonic acid activation .…”
mentioning
confidence: 99%